The ethnobotanics of medicinal plants and their deterioration in a community in the mountains of Peru - Acosta-Román, Mercedes (2023)
Objective: Ethnobotanically identify medicinal plants and their tendency to deteriorate the Andean Community by Daniel Hernández. Methodology: Descriptive study, population of 438 families and a sample of 205 families from the Andean Community of Daniel Hernández, Huancavelica, Peru; The semi-structured interview technique was used, subsequently the collection of medicinal plants provided by the interviewees was carried out; Then, taxonomic determinations were carried out, thus obtaining information regarding the diseases that are treated with medicinal plants, according to the WHO; In the determination of medicinal species with a tendency to deterioration, they are classified according to the following: Level I (very low level) less than 10; Level II (low level) 11 to 20; Level III (medium level) 21 to 30; Level IV (high level) 31 to 40; and, Level V (very high level) greater than 41. Results: The medicinal plants used are reported, being 63 families, 142 genera and 144 species; Also, the diversity of medicinal plants with a tendency to deterioration is reported, with 53 families, 93 genera and 101 species, cataloged at level V of deteriorating species. Conclusions: A high diversity of medicinal plants found in the Andean Community of Daniel Hernández, which present a high level with a tendency towards population loss of medicinal plant species.